Lonizing radiation effects in mos oxides - Oldham, Timothy R (Singapore World Scientific, 1999)
This volume is intended to serve as an updated critical guide to the extensive literature on the basic physical mechanisms controlling the radiation and reliability responses of MOS oxides.
Keywords: Cơ bản